JOB HOPPING BEHAVIOR IN MILLENNIALS - Didin Hikmah Perkasa; Setiyo Purwanto (ZILLZELL MEDIA PRIMA, 2024)
This study aims to analyze the Effect of Job Satisfaction on Employee Loyalty and Job Hopping Behavior or changing jobs in the Millennial Generation in Jakarta. The object of research was carried out to employees of fast food restaurants in Jakarta. The research design used a causal quantitative research design. The population in this study was millennial employees who worked in fast food restaurants as many as 100 people, while the sample used was as many as 100 people using non-probability sampling with jenu sampling techniques. The data collection method uses the survey method, with the research instrument being a questionnaire. Data analysis methods using SEM Pls test outer model, inner model and hypothesis test. The first stage determines the indicators for each variable. The second stage tests the validity and reliability of each variable studied. The results of this study prove that job satisfaction and job loyalty negatively affect job hopping behavior. While job satisfaction has a positive effect on job loyalty.